Advancing student nurse knowledge of the biomedical sciences: A mixed methods study. (January 2017) - Craft, Judy; Christensen, Martin; Bakon, Shannon; Wirihana, Lisa
Abstract: Background: Nursing students' ability to learn, integrate and apply bioscience knowledge to their clinical practice remains a concern. Objectives: To evaluate the implementation, influence, and student perspective of a team-teaching workshop to integrate bioscience theory with clinical nursing practice. Design: The team-teaching workshop was offered prior to commencement of the university semester as a refresher course at an Australian university. This study employed a sequential explanatory mixed methods design incorporating both quantitative and qualitative items. Methods: An evaluation survey with quantitative and qualitative items and a focus group were employed. The qualitative data were analysed using a thematic approach. The quantitative data was combined with the emergent themes in the qualitative data. Participants: Participants were final year nursing students. Nine students attended the workshop. All students completed the evaluation ( N = 9) and 44.4% ( N = 4) attended the focus group. Results: The results revealed six themes: (1) lectures are an inadequate teaching strategy for bioscience; (2) teaching strategies which incorporate active learning engage students; (3) the team-teaching workshop provides an effective learning environment; (4) the workshop content should be expanded; (5) pharmacology should relate to bioscience, and bioscience should relate to nursing; and (6) team-teaching was effective in integrating pharmacology with bioscience, and then translating this into nursing practice. Students had felt there was disjointedness between pharmacology and bioscience, and between bioscience and nursing care within their undergraduate studies. The workshop that was based on team-teaching bridged those gaps, utilised active learning strategies and provided an effective learning environment. Conclusion: Team-teaching that employs active learning strategies is an effective approach to assist nursing students to integrate bioscience knowledge into their nursing practice. Highlights: Nursing students' continue to experience difficulty translating bioscience knowledge into the clinical environment. Team-teaching employing a biomedical scientist and a nursing academic may assist in bridging the bioscience theory practice gap. Innovative teaching strategies that assist in consolidating learnt theory to nursing practice need to be explored. Nursing education needs to be delivered cohesively to facilitate integration of bioscience and nursing concepts.